Religious political arguments, accessibility, and democratic deliberation - Billingham, P (Notre Dame Law School, 2023)
Christian critics of liberalism, and especially of contemporary public-reason liberalism, often argue that it objectionably excludes religious voices form the public square, by requiring citizens to bracket their religious convictions when they engage in democratic deliberation. In response, liberals often deny that their views have this implication. Many public-reason liberal theorists are “inclusivists,” who permit religious contributions to deliberation. Yet even inclusivists provide little reason to think that religious political arguments can be persuasive or fruitful. After all, they tend to see religious reasons as inaccessible to others, due to relying on beliefs, values, and methods of reasoning that others do not share. Other citizens are seemingly unable to assess their validity, critically engage with them, or be persuaded by them. This Article challenges this view. It seeks to show that other citizens can meaningfully engage with religious political arguments, such that those arguments can play a productive and persuasive role within public deliberation and in ways that can ultimately shape the content of laws. All of this can be true even if religious arguments do not meet the standard of accessibility required to qualify as public reasons. To make this case, I discuss two arguments from Christian theologians. The Article speaks to two audiences. First, it shows that liberals (including public-reason liberals) should positively welcome religious arguments within democratic deliberation. Liberalism, on its own terms, should be more open to religious reasoning than is commonly assumed. Second, this shows that Christian critics of liberalism can be answered, on this point at least.